2020
DOI: 10.3390/horticulturae6010012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vine Water Status and Exogenous Abscisic Acid on Berry Composition of Three Red Wine Grapes Grown under Mediterranean Climate

Abstract: Beyond climatic conditions, qualitative performance is led by the intrinsic characteristics of the genotype. The aim of this study was to investigate the relationship between vine water status and exogenous abscisic acid (ABA) application on berry composition of the cultivars Cannonau, Merlot and Sangiovese. The experiment, carried out in 2016 and 2017, consisted of comparing two levels of irrigation treatments, full irrigation versus a non-irrigation treatment. Within each treatment, two sub-treatments were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Vintage-dependent variations were also observed in the grape juice components. However, whilst biostimulant application was found to have a limited effect on the berry sugar content in other studies [38,56], we observed that the highest doses of ABA and CHT resulted in an increased TSS level in 2019, while both of the doses of biostimulants caused a decreased TSS level at the harvest of 2020. On the contrary, berries from the treated vines exhibited a lower TA level than those from the untreated vines at the harvest stage of 2019, while the opposite effect was observed in the following vintage.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Vintage-dependent variations were also observed in the grape juice components. However, whilst biostimulant application was found to have a limited effect on the berry sugar content in other studies [38,56], we observed that the highest doses of ABA and CHT resulted in an increased TSS level in 2019, while both of the doses of biostimulants caused a decreased TSS level at the harvest of 2020. On the contrary, berries from the treated vines exhibited a lower TA level than those from the untreated vines at the harvest stage of 2019, while the opposite effect was observed in the following vintage.…”
Section: Discussioncontrasting
confidence: 69%
“…It is known that high temperatures decrease the accumulation of the anthocyanin, phenolic and volatile compounds, and it has been suggested that specific secondary metabolites (e.g., kaempferol and flavonols in general) could be indicators of fruit quality losses associated with warming [62]. The beneficial effect of exogenously applied biostimulants on grape composition can be achieved during moderate climate conditions [63], while the effect is limited under a hot and dry climate [56]-similar to the local weather conditions observed at the experimental vineyard during the ripening period of the second vintage.…”
Section: Discussionmentioning
confidence: 99%
“…Among cultural practices, water status management is considered one of the most important tools to increase polyphenols content and to improve the quality of red grapes [7,20,[33][34][35][36][37]. It is generally considered that deficit irrigation regimes stimulate synthesis and favor the concentration of phenolic compounds in grapes [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Food and Agriculture Organization [92], Bulgaria was sixteenth in the world for cherry production in 2018 and twenty-first for wine (about 93% of the produced wine grapes are used for wine production [93]). The irrigation of these crops is very important for their quality [94,95], and for both cultures the drip irrigation method shows best results [96,97]. The irrigation norm for the crops is the same [98,99]-6 L/m 2 /daybut the periods of irrigation differ: 15 March to 1 September for cherries and 1 June to 1 September for wine grapes.…”
Section: Application Hypothesesmentioning
confidence: 99%